Gradient-coated lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof

The conductivity and cyclic performance of lithium manganese iron phosphate material are improved through the ladder coating method, and the poor conductivity and manganese ion dissolution problems are solved, high rate performance and long cycle life are achieved, and it is suitable for lithium-ion battery positive electrode materials.

CN119252899APending Publication Date: 2025-01-03SHANGHAI NAT ENG RES CENT FORNANOTECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411410080.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The poor conductivity of lithium manganese iron phosphate materials and the dissolution of manganese ions lead to insufficient rate performance and cycle stability.

Method used

The ladder coating method is adopted, and the initial raw material solid-phase ball milling, two and three ball milling treatments are processed, and sintered at high temperature to form a multi-layer carbon coating structure to improve the conductivity and cycling performance of the material.

Benefits of technology

It significantly improves the conductivity and rate performance of lithium manganese iron phosphate material, extends its cycle life, meets battery-grade usage requirements, reduces the cost of raw materials and instruments, and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses an echelon-coated lithium iron manganese phosphate positive electrode material and a preparation method and application thereof, and relates to the field of lithium ion batteries. The preparation method comprises the following steps: mixing a lithium source, an iron source, a manganese source, phosphate and a carbon source, and carrying out ball milling treatment; performing drying, grinding and low-temperature sintering on the ball-milled raw materials to obtain a precursor I; putting the precursor I and a carbon source into a ball mill, and carrying out spheroidal graphite treatment; sintering the ball-milled raw materials to obtain a precursor II; putting the precursor II and a carbon source into a ball mill, and carrying out third-time ball milling; and sintering the ball-milled raw materials, and sintering to obtain the high-temperature-resistant ceramic material. By adopting the echelon coating preparation method, the electrical property of the lithium manganese iron phosphate positive electrode material is improved, the cycle performance and the rate capability of the lithium manganese iron phosphate are improved, the cost of raw materials and instruments is low, the production efficiency is high, and large-scale production can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium-ion batteries, and in particular relates to a sequentially coated lithium manganese iron phosphate positive electrode material and a preparation method and application thereof. Background Art

[0002] In recent years, as an upgraded alternative material to lithium iron phosphate, lithium manganese iron phosphate (LMFP, LiMn 1-x Fe x PO4) has attracted much attention from the market. Lithium manganese iron phosphate is a high-voltage (4.1 V) phosphate material. It is doped with a certain amount of manganese on the basis of lithium iron phosphate, and the voltage platform of the material is increased by adjusting the manganese-iron ratio. It has similar properties to lithium iron phosphate and lithium manganese phosphate. Compared with lithium iron phosphate, lithium manganese iron phosphate has better thermal stability, chemical stability and economy, and also has higher energy density. Therefore, in recent years, researchers have extensively studied lithium manganese iron phosphate and believe that it is expected to become a new generation of high-energy density power battery positive electrode material. However, there are still some problems to be solved in the use of lithium manganese iron phosphate: 1) Due to the limitations of structural characteristics, its conductivity is poor and the lithium ion diffusion rate is low, which in turn affects the rate performance; 2) The Jahn-Teller effect promotes manganese precipitation, resulting in the attenuation of the material cycle life and reduced cycle stability. At present, the methods for improving the performance of lithium manganese iron phosphate materials mainly include material nano-sizing, carbon coating and ion doping. Material nano-sizing can make the material contact with the electrolyte more fully, shorten the lithium ion migration path, and thus improve the charge and discharge capacity and rate performance of the material. At the same time, the electrochemical properties of the material can also be improved by designing a special morphology. Carbon coating can effectively build a fast conductive network by evenly coating the carbon coating on the surface of the material, providing an effective channel for Li+ diffusion, improving the conductivity of the material, and inhibiting the growth and agglomeration of crystal particles. By doping ions in the material, defects can be generated in the original lattice, making Li + The diffusion channel expands and the carrier density of the material increases, thereby improving the conductive properties of the material itself. Summary of the invention

[0003] The present invention aims to provide a sequentially coated lithium iron manganese phosphate positive electrode material to improve the current problems of low conductivity of lithium iron manganese phosphate material and dissolution of manganese ions.

[0004] Another object of the present invention is to provide a method for preparing the above-mentioned step-by-step coated lithium manganese iron phosphate positive electrode material product.

[0005] Another object of the present invention is to provide an application of the above product.

[0006] The object of the present invention is achieved through the following scheme: a cascade-coated lithium iron manganese phosphate positive electrode material, wherein the chemical formula of the lithium iron manganese phosphate is LiMn1-xFexPO4, and the positive electrode material is a cascade-coated positive electrode material.

[0007] The present invention provides a method for preparing a lithium manganese iron phosphate positive electrode material coated in stages, comprising the following steps: Solid phase ball milling of initial raw materials: 1) Mixing a lithium source, a manganese source, an iron source, a phosphorus source, a carbon source and ethanol in a ball mill according to a certain ratio, and performing ball milling treatment, wherein the raw materials of the lithium iron manganese phosphate slurry are mixed in a molar ratio of lithium: manganese: iron: phosphorus of 1:0.6:0.4:1; 2) After ball milling, the material is dried and sintered to obtain precursor 1; Secondary coating: 3) Transferring the precursor 1 and the carbon source to the planetary ball mill again for ball milling; 4) Drying and sintering the ball-milled precursor to obtain precursor 2; Three times wrapping: 5) transferring the precursor II and the carbon source III to a planetary ball mill for ball milling; 6) Dry and sinter the ball-milled precursor to obtain the desired positive electrode material.

[0008] The first step of the present invention is to obtain a primary carbon-coated ferromanganese phosphate precursor 1, the second step is to crush the precursor 1 and then carbon-coat it to obtain a double-coated precursor 2, the third step is to crush the precursor 2 and then implement three-layer coating, and obtain a cascade-coated positive electrode material after sintering. This method ensures the consistency of the ferromanganese phosphate material and the coated Junyuning, greatly improving the consistency of the product. At the same time, the cascade phosphoric acid improves the conductivity of the material, greatly improves its rate performance and cycle performance, and meets the battery-level use requirements.

[0009] Furthermore, in step (1), the lithium source is any one or two or more of lithium carbonate, lithium hydroxide, and lithium phosphate; the manganese source is any one or two or more of manganese sulfate, manganese carbonate, and manganese tetraoxide; the iron source is any one or two or more of ferric phosphate, ferrous oxalate, and ferrous sulfate; and the phosphorus source is any one or two or more of diammonium phosphate, diammonium hydrogen phosphate, ferric phosphate, and phosphoric acid.

[0010] Furthermore, in step (1), the lithium source, manganese source, iron source and phosphorus source are mixed in a proportion, wherein the ratio of beads to material is 12:1.

[0011] Furthermore, in the solid phase ball milling preparation step of the initial raw material, the drying temperature of the vacuum drying oven is 50°C to 85°C, and the drying time is 4 h to 12 h.

[0012] Furthermore, in step 2), the sintering temperature of the vacuum tube furnace is 200°C to 400°C, and the sintering time is 1 h to 3 h.

[0013] Furthermore, in step 4), the sintering temperature of the vacuum tube furnace is 400°C to 550°C, and the sintering time is 2 h to 5 h.

[0014] Furthermore, in step 6), the sintering temperature of the vacuum tube furnace is 600°C to 800°C, and the sintering time is 5 h to 8 h.

[0015] Furthermore, the rotation speed of the planetary ball mill in the preparation step is 200 r / min ~ 500 r / min.

[0016] The present invention also provides an application of the sequentially coated lithium manganese iron phosphate as a positive electrode material in a lithium battery.

[0017] The present invention adopts a step-by-step coating preparation method, which improves the electrical properties of the lithium iron manganese phosphate positive electrode material, improves the cycle performance and rate performance of the lithium iron manganese phosphate, and has low raw material and instrument costs, high production efficiency, and can achieve large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is the cycle performance diagram of Example 1; Figure 2 Comparison of impedance performance between Example 1 and Comparative Example 1; Figure 3 Example 1 rate performance diagram; Figure 4 SEM images of Example 1 and Comparative Example 2. DETAILED DESCRIPTION

[0019] In order to further explain the technical solution of the present invention, the present invention is described in detail with reference to specific implementation cases below.

[0020] Example 1 A sequentially coated lithium manganese iron phosphate positive electrode material, the chemical formula is LiMn 1-x Fe x PO4 is prepared as follows: Solid phase ball milling of initial raw materials: 1) Lithium carbonate, ferrous sulfate, manganese sulfate and ammonium dihydrogen phosphate were mixed in a molar ratio of 1.0:0.6:0:4:1.0 and glucose with a mass concentration of 8 wt% in a ball mill, and the mass ratio of beads to materials was 12:1. Ethanol was added to the mixed raw materials, and the mixture was ball milled to obtain a primary coating slurry. The ball milling was performed for 12 hours at a rotation speed of 450 r / min. 2) The ball-milled slurry was transferred to an oven and baked at 60°C for 5 hours. The dry powder was taken out and transferred to a tube furnace and calcined at 300°C for 2.5 hours to obtain precursor 1. Secondary coating: 3) The precursor obtained in step 2) was transferred to a ball mill, 3 wt% glucose was added, and ethanol was added for ball milling to obtain a secondary coating slurry, which was ball milled for 12 hours at a speed of 450 r / min; 4) The ball-milled slurry was transferred to an oven and baked at 60°C for 5 hours. The dry powder was taken out and transferred to a tube furnace and calcined at 450°C for 1.5 hours to obtain precursor 2. Three times wrapping 5) Transfer the obtained precursor 2 to a ball mill, add 1wt% glucose, add ethanol and perform ball milling three times to obtain the coated slurry, and ball mill for 12 hours at a speed of 450 r / min; 6) The ball-milled slurry was transferred to an oven and baked at 60°C for 5 hours. The dry powder was taken out and transferred to a tube furnace for calcination at a temperature of 680°C for 6.5 hours to obtain a step-by-step coated lithium manganese iron phosphate positive electrode material.

[0021] Example 2 A sequentially coated lithium manganese iron phosphate positive electrode material is prepared according to the following steps: Solid phase ball milling of initial raw materials 1) lithium carbonate, ferrous sulfate, manganese sulfate and dihydrogen phosphate in a molar ratio of 1.0:0.6:0:4:1.0 and 8 wt% glucose were mixed in a ball mill, wherein the mass ratio of beads to materials was 12:1, ethanol was added to the mixed raw materials, and ball milling was performed to obtain a primary coating slurry, and the ball milling was performed for 12 hours at a rotation speed of 450 r / min; 2) After the ball-milled slurry was transferred to an oven and baked at 60°C for 5 hours, the dry powder was taken out and transferred to a tube furnace and calcined at 300°C for 2.5 hours to obtain precursor 1; Secondary coating: 3) The precursor obtained in step 2) was transferred to a ball mill, 1 wt% glucose was added, and ethanol was added for ball milling to obtain a secondary coating slurry, and the ball milling was performed for 12 hours at a speed of 450 r / min; 4) The ball-milled slurry was transferred to an oven and baked at 60°C for 5 hours. The dry powder was taken out and transferred to a tube furnace and calcined at 450°C for 1.5 hours to obtain precursor 2. Three times wrapping 5) The precursor 2 obtained in step 2) was transferred to a ball mill, 1 wt% glucose was added, and ethanol was added for ball milling to obtain a three-time coating slurry, and the ball milling was performed for 12 hours at a speed of 450 r / min; 6) The ball-milled slurry was transferred to an oven and baked at 60°C for 5 hours. The dry powder was taken out and transferred to a tube furnace for calcination at a temperature of 680°C for 6.5 hours to obtain a step-by-step coated lithium manganese iron phosphate positive electrode material.

[0022] Example 3 A sequentially coated lithium manganese iron phosphate positive electrode material is prepared according to the following steps: Solid phase ball milling of initial raw materials 1) Mix lithium carbonate, ferrous sulfate, manganese sulfate and dihydrogen phosphate in a molar ratio of 1.0:0.6:0:4:1.0 and 8wt% of glucose in a ball mill, wherein the bead: material mass ratio is 12:1, add ethanol to the mixed raw materials, perform ball milling to obtain a primary coating slurry, and ball mill for 12 hours at a rotation speed of 450 r / min; 2): The ball-milled slurry was transferred to an oven and baked at 60°C for 5 hours. The dry powder was taken out and transferred to a tube furnace and burned at 300°C for 2.5 hours to obtain precursor 1; Secondary coating: 3) The precursor obtained in step 2) was transferred to a ball mill, 5 wt% glucose was added, and ethanol was added for ball milling to obtain a secondary coating slurry, and the ball milling was performed for 12 hours at a speed of 450 r / min; 4) The ball-milled slurry was transferred to an oven and baked at 60°C for 5 hours. The dry powder was taken out and transferred to a tube furnace and calcined at 450°C for 1.5 hours to obtain precursor 2. Three times wrapping 5) The precursor 2 obtained in step 2) was transferred to a ball mill, 1 wt% glucose was added, and ethanol was added for ball milling to obtain a three-time coating slurry, and the ball milling was performed for 12 hours at a speed of 450 r / min; 6) The ball-milled slurry was transferred to an oven and baked at 60°C for 5 hours. The dry powder was taken out and transferred to a tube furnace for calcination at a temperature of 680°C for 6.5 hours to obtain a step-by-step coated lithium manganese iron phosphate positive electrode material.

[0023] Comparative Example 1 A three-coated lithium manganese iron phosphate positive electrode material, similar to Example 1, the first layer of carbon coating is thinner, and the second layer of carbon coating is thicker; and the sintering temperature of the first coating and the second coating is 450° C., and the material is prepared according to the following steps: Solid phase ball milling of initial raw materials 1) Lithium carbonate, ferrous sulfate, manganese sulfate and dihydrogen phosphate (ratio 1.0:0.6:0:4:1.0) and 3 wt% glucose were mixed in a ball mill (bead: material = 12:1), ethanol was added to the mixed raw materials, and ball milling was performed for 12 hours at a speed of 450 r / min; 2) The ball-milled slurry was transferred to an oven and baked at 60°C for 5 hours. The dry powder was taken out and transferred to a tube furnace and calcined at 450°C for 2.5 hours to obtain precursor 1. Secondary coating: 3) The precursor obtained in step 2) was transferred to a ball mill, 8 wt% glucose and ethanol were added for ball milling for 12 hours at a speed of 450 r / min; 4) The ball-milled slurry was transferred to an oven and baked at 60°C for 5 hours. The dry powder was taken out and transferred to a tube furnace and calcined at 450°C for 1.5 hours to obtain precursor 2. Three times wrapping 5) Transfer the precursor 2 to a ball mill, add 1wt% glucose, add ethanol and perform ball milling for 12 hours at a speed of 450 r / min; 6) The ball-milled slurry was transferred to an oven and baked at 60°C for 5 hours. The dry powder was then taken out and transferred to a tube furnace for calcination at a temperature of 650°C for 12 hours.

[0024] Comparative Example 2 A carbon-coated lithium manganese iron phosphate positive electrode material, compared with Example 1, is coated with only one layer and is prepared according to the following steps: Solid phase ball milling of initial raw materials 1) Lithium carbonate, ferrous sulfate, manganese sulfate and dihydrogen phosphate were mixed in a ball mill at a molar ratio of 1.0:0.6:0:4:1.0 and 8 wt% glucose, with a bead: material mass ratio of 12:1. Ethanol was added to the mixed raw materials and ball milled for 12 hours at a speed of 450 r / min. 2) The ball-milled slurry was transferred to an oven and baked at 60°C for 5 hours. The dry powder was taken out and transferred to a tube furnace and calcined at 680°C for 6.5 hours to obtain a single carbon-coated lithium manganese iron phosphate positive electrode material.

[0025] Comparative Example 3 A secondary carbon-coated lithium manganese iron phosphate positive electrode material is prepared according to the following steps: Solid phase ball milling of initial raw materials 1) Lithium carbonate, ferrous sulfate, manganese sulfate and dihydrogen phosphate were mixed in a ball mill at a molar ratio of 1.0:0.6:0:4:1.0 and 7 wt% glucose, with a bead: material mass ratio of 12:1. Ethanol was added to the mixed raw materials and ball milled for 12 hours at a speed of 450 r / min. 2) The ball-milled slurry was transferred to an oven and baked at 60°C for 5 hours. The dry powder was then taken out and transferred to a tube furnace and calcined at 300°C for 2.5 hours to obtain precursor 1.

[0026] Secondary coating: 3) The precursor obtained in step 2) was transferred to a ball mill, 3 wt% glucose and ethanol were added for ball milling for 12 hours at a speed of 450 r / min; 4) The ball-milled slurry was transferred to an oven and baked at 60°C for 5 hours. The dry powder was taken out and transferred to a tube furnace and calcined at 680°C for 6.5 hours to obtain a secondary carbon-coated lithium manganese iron phosphate positive electrode material.

[0027] The electrochemical properties of the lithium manganese iron phosphate positive electrode materials prepared in the examples and comparative examples were tested, and the specific method is as follows: The tests were conducted based on CR2032 button cells, using lithium metal sheets as counter electrodes, PE / PP as separators, and LiPF6 as electrolyte; follow the steps below: (1) The active material, the conductive agent and polyvinylidene fluoride (PVDF) were mixed and ground in a mass ratio of 8:1:1, and N-methyl-2-pyrrolidone (NMP) was used as a solvent; (2) coating the slurry after grinding in step (1) on aluminum foil using a preparation device to control the thickness to 200 μm, and then transferring it to a vacuum oven at 120° C. and drying it for 12 h; (3) The electrodes were cut into small discs with a diameter of 12 mm and transferred to a glove box filled with argon gas to be assembled into button cells.

[0028] Impedance performance test method: Under normal temperature, the battery disturbance voltage is 5mV, and the scanning frequency is 0.1-100kHz; Cycle performance test method: Under normal temperature, the battery is charged to 4.5V at a current density of 0.2C, then switched to 4.5V constant voltage charging. When the charging current is less than 0.05C, the charging is cut off; let it stand for 10 minutes, then discharge to 2.8V at a current density of 0.2C; let it stand for 10 minutes. Repeat the above steps to complete 300 cycles As shown in Table 1, the lithium ion battery prepared by the nano-manganese iron lithium phosphate obtained in the present invention exhibits good electrochemical performance. Among them, the lithium ion battery prepared by the nano-manganese iron lithium phosphate obtained in Example 1 has an initial discharge capacity of 155 mAhg -1 , the first coulombic efficiency is 86.3%. Figure 1 The capacity retention rate of Example 1 is still 96% after 300 cycles. Figure 2 As shown, the impedance of Example 1 is superior to that of Comparative Example 1, which illustrates the influence of the temperature of successive coating on the impedance performance. Figure 3 As shown in the rate performance diagram of Example 1, its 0.2C specific capacity is nearly 150 mA·h / g, 10C specific capacity is 110 mA·h / g, and then returns to 0.1C specific capacity of 150 mA·h / g, showing excellent rate performance. Figure 4 It is known that the particle size of the positive electrode material coated in stages is at the nanometer level, while the particle size of the positive electrode material coated once in Comparative Example 2 is at the micrometer level, and the particle uniformity of the material coated in stages is better.

[0029] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the technical solution of the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A sequentially coated lithium manganese iron phosphate positive electrode material, characterized in that: The chemical formula of the lithium iron manganese phosphate is LiMn 1-x Fe x PO4, the positive electrode material is obtained by sequential coating.

2. A method for preparing the sequentially coated lithium manganese iron phosphate positive electrode material as claimed in claim 1, characterized in that: The following steps are involved: Solid phase ball milling of initial raw materials: 1) Mixing a lithium source, a manganese source, an iron source, a phosphorus source, a carbon source and ethanol in a ball mill, wherein the raw materials of the lithium iron manganese phosphate slurry are mixed and ball milled in a molar ratio of lithium: manganese: iron: phosphorus of 1:0.6:0.4:1, and the carbon source is one or two or more of glucose, sucrose, citric acid, graphene, carbon nanotubes, etc.; 2) The ball-milled material is dried and sintered to obtain precursor 1; Secondary coating: 3) Transferring the precursor 1 and the carbon source to the planetary ball mill again for ball milling; 4) Drying and sintering the ball-milled material to obtain precursor 2; Three times wrapping: 5) transferring the precursor 2 and the carbon source to a planetary ball mill for a third time for ball milling; 6) Dry and sinter the milled material to obtain the desired positive electrode material.

3. The method for preparing the sequentially coated lithium iron manganese phosphate positive electrode material according to claim 2, characterized in that: In step 1), the lithium source is any one or two or more of lithium carbonate, lithium hydroxide, and lithium phosphate; the manganese source is any one or two or more of manganese sulfate, manganese carbonate, and manganese tetraoxide; the iron source is any one or two or more of ferric phosphate, ferrous oxalate, and ferrous sulfate; the phosphorus source is any one or two or more of diammonium phosphate, diammonium hydrogen phosphate, ferric phosphate, and phosphoric acid.

4. The method for preparing the sequentially coated lithium manganese iron phosphate positive electrode material according to claim 2, characterized in that: In the preparation step 2), the drying temperature of the vacuum drying oven is 50°C to 85°C, and the drying time is 4 h to 12 h.

5. The method for preparing the sequentially coated lithium manganese iron phosphate positive electrode material according to claim 2, characterized in that: In step 2), the sintering temperature of the vacuum tube furnace is 200°C to 400°C, and the sintering time is 1 h to 3 h.

6. The method for preparing the sequentially coated lithium manganese iron phosphate positive electrode material according to claim 2, characterized in that: In step 4), the sintering temperature of the vacuum tube furnace is 400°C to 550°C, and the sintering time is 2 h to 5 h.

7. The method for preparing the sequentially coated lithium manganese iron phosphate positive electrode material according to claim 2, characterized in that: In step 4), the sintering temperature of the vacuum tube furnace is 600°C to 800°C, and the sintering time is 5 h to 8 h.

8. The method for preparing the sequentially coated lithium manganese iron phosphate positive electrode material according to claim 2, characterized in that: In the preparation step 5), the rotation speed of the planetary ball mill is 200 r / min to 500 r / min, and the carbon source is one or two or more of glucose, sucrose, citric acid, graphene, carbon nanotubes, etc.

9. Use of the sequentially coated lithium manganese iron phosphate according to claim 1 as a positive electrode material in a lithium battery.